2012
DOI: 10.1038/nsmb.2312
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodelers Isw1 and Chd1 maintain chromatin structure during transcription by preventing histone exchange

Abstract: Set2-mediated methylation of histone H3 Lys36 (H3K36) is a mark associated with the coding sequences of actively transcribed genes, yet plays a negative role during transcription elongation. It prevents trans-histone exchange over coding regions and signals for histone deacetylation in the wake of RNA polymerase II (RNAPII) passage. We have found that in Saccharomyces cerevisiae the Isw1b chromatin-remodeling complex is specifically recruited to open reading frames (ORFs) by H3K36 methylation through the PWWP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
329
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(359 citation statements)
references
References 50 publications
19
329
1
Order By: Relevance
“…Chromatin is quickly reassembled after passing through the transcription machinery (59,60), and hyperacetylation or lack of chromatin remodelers induces cryptic bidirectional transcription by Pol II (61,62). It would be interesting to explore whether Pol III also contributes to these cryptic bidirectional transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin is quickly reassembled after passing through the transcription machinery (59,60), and hyperacetylation or lack of chromatin remodelers induces cryptic bidirectional transcription by Pol II (61,62). It would be interesting to explore whether Pol III also contributes to these cryptic bidirectional transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae, Set2-mediated H3K36me3 maintains a hypoacetylation state of transcribed genes (28,29,31,32), especially for genes with long sequence and transcribed less often (44). Based on these studies, we wondered whether SET-2 affects the histone acetylation level at frq locus.…”
Section: Deletion Of Set-2 Results In Hyperacetylation Of Frq Open Rementioning
confidence: 99%
“…It is conceivable that the role of H3K36me2 in splicing is directly connected to the ability of this mark to maintain a suppressed chromatin environment through the recruitment of Rpd3S and Isw1b. [37][38][39][40][41] Indeed, deletion of RPD3, which encodes a member of the Rpd3 complex, 75-77 also leads to modest splicing defects, which could imply that histone deacetylation and chromatin remodeling (i.e., creation of a particular chromatin environment) plays a key role in snRNP recruitment. Another possibility is the potential role of H3K36 methylation in affecting some aspect of RNA Pol II elongation or termination.…”
Section: Discussionmentioning
confidence: 99%
“…36 Studies show that Set2 is associated with the elongating form of RNA Pol II and mediates H3K36me2/me3 to recruit a number of chromatin-modifying complexes (Rpd3S and Isw1b) that maintain a repressive chromatin environment that is resistant to pervasive transcription in the coding regions of genes. [37][38][39][40][41][42] Although a number of studies have shown that the human homolog of Set2, SETD2, is important for alternative splicing 31,33 and that H3K36 is essential for viability in drosophila, 43 the direct role of H3K36me3 and other methylation states (particularly H3K36me2) in both canonical and alternative splicing has not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%